Supporting Elementary Students' Science Achievement in Electrical Energy Through Student Teams-Achievement Divisions Cooperative Learning - Wijitra Chanthaket; Prasart Nuangchalerm (PT. Pusmedia Group Indonesia, 2026)
This experimental research, a one-group pretest-posttest design aims to enhance third-grade students' understanding of electrical energy and their academic performance by implementing the STAD approach to cooperative learning. The initiative will focus on the study of science both before and after students acquire knowledge of electrical energy through technical cooperative learning management. Additionally, the study aims to examine students' satisfaction with the management of cooperative learning. The participants were 32 of grade 3 students in the second semester of the 2025 academic year, selected using a cluster random sampling process. Instruments used to analyze 20 science accomplishment assessments included a learning management strategy for the science subject of electrical energy. The instruments included the STAD science lesson plan and a satisfaction questionnaire regarding cooperative learning management. The results indicated that the performance in science topics post-test was statistical significantly higher than pre-test at .05. Furthermore, the satisfaction level of third-grade students with the science lesson on electrical energy, taught using the STAD cooperative learning was found to be highest level. The study can be used for teachers to leverage students’ learning achievement and guide students in classroom collaborating.